2019
DOI: 10.1038/s41598-019-52051-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiplex and sensitive lateral flow immunoassay for the diagnosis of periprosthetic joint infection

Abstract: The diagnosis of periprosthetic joint infection (PJI) remains a challenge. However, recent studies showed that synovial fluid biomarkers have demonstrated greater diagnostic accuracy than the currently used PJI diagnostic tests. In many diagnostic tests, combining several biomarkers into panels is critical for improving diagnostic efficiency, enhancing the diagnostic precision for specific diseases, and reducing cost. In this study, we prove that combining alpha-defensin and C-reactive protein (CRP) as biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Even with ULOC-enabled sample dilution (DF x 20), high-concentration LFIA effects are observed, affirming the necessity of dilution to avoid false-negative results. The majority of LFIA developers recommend an assay duration of up to 20 min to allow the signal to reach full stability and sensitivity [ 8 ]. However, we found that a 15 min duration was suitable for allowing signals to develop for all concentrations, without neglecting more concentrated samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with ULOC-enabled sample dilution (DF x 20), high-concentration LFIA effects are observed, affirming the necessity of dilution to avoid false-negative results. The majority of LFIA developers recommend an assay duration of up to 20 min to allow the signal to reach full stability and sensitivity [ 8 ]. However, we found that a 15 min duration was suitable for allowing signals to develop for all concentrations, without neglecting more concentrated samples.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the lateral flow immunoassay (LFIA) is the most successful application of consumer diagnostics [ 6 ]. Combining LFIAs with smartphones as optical detectors allow for ‘on-the-go’ decentralized screening [ 7 ] and smartphones can even provide semi-quantitative results by calibrating test and control line intensity values toward a particular antigen concentration [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, multiple test lines can be used for simultaneous detection of different targets (Song et al, 2014). For instance, Tsai et al developed a multiplex and sensitive lateral flow assay for simultaneous detection of alpha-defensin and C-reactive protein (Tsai et al, 2019).…”
Section: Lateral Flow Stripsmentioning
confidence: 99%
“…The existing methods for infection diagnosis mainly involved microbial culture [31] and non-culture methods, including bacterial staining, white blood cell counting, antibody and antigen immunoassay, and next generation sequencing (mNGS) [32][33][34][35][36][37]. These methods are of high diagnostic value but require complex specialized equipment, special site environment and professional staff.…”
Section: Introductionmentioning
confidence: 99%